Secondary succession toward woodland - Changes in the herb layer species composition - Dostálová, Alena (Jihočeská univerzita, 2011)
This dissertation focus on spontaneously developed forests (SDFs) on mesic stands. The present tree layer was described and the possible changes in the tree layer was estimated. Influence of site- and context-dependent factors on the species composition and general character of the herb layer was studied in detail. An experiment was established to study seed and safe-site limitation of nine forest herb species.
Secondary succession toward woodland - Changes in the herb layer species composition
Změny bylinného patra v průběhu sekundární sukcese lesa
Keywords: sekundární sukcese; bylinné patro; semenáčky stromů; lesní druhy; náletové dřeviny; secondary succession; herb layer; tree seedlings; woodland species; forest species; spontaneously developed forest